Peran Citizen Journalism dalam Partisipasi Publik pada Pilkada 2024 di Kabupaten Wakatobi - Sultrayansa Sultrayansa; Sarinah Sarinah (CV. ITTC INDONESIA, 2025)
Citizen journalism in the 2024 Regional Head Election in Wakatobi Regency is an interesting phenomenon as a form of public participation in the democratic process. With the development of digital technology, people no longer only act as consumers of information, but also as producers of political information through social media and digital platforms. This research aims to identify the role of citizen journalism in increasing public participation in the implementation of Regional Head Elections in Wakatobi Regency. This research uses a qualitative approach with a descriptive study design. Data were collected through in-depth interviews, participatory observation, and content analysis of citizen journalism circulating during the 2024 Regional Head Election campaign period. The research subjects involved citizen journalism actors, active voters, and stakeholders. Data analysis techniques were carried out through data reduction. The results showed that citizen journalism contributed significantly to increasing transparency, political education and social control during the Wakatobi Regional Head Election. People were more active in voicing issues of violations, political discrimination, and mass mobilization through videos and social media posts. However, the main challenge remains low digital literacy and the risk of spreading disinformation. Synergy between professional journalists and citizen journalism is needed to ensure the accuracy and objectivity of information. With citizen journalism, the people of Wakatobi have shown a role transformation from passive voters to active actors in maintaining the integrity of the democratic process. This research recommends the need for increased media literacy capacity and multi-stakeholder synergy so that citizen journalism can become a tool for strengthening inclusive and responsible local democracy.